2021
DOI: 10.1002/er.7095
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of an accumulator unit using phase change material with a fixed volume of fins

Abstract: Summary Melting rate enhancement inside an accumulator unit for a phase change material (PCM) has been numerically investigated in a shell‐and‐tube (S‐T) arrangement that incorporates the circular type of fins, considering a fixed total volume of fins. The number of fins was chosen as the design parameter. The heat transfer fluid (HTF) was chosen as water that flows through the selected accumulator unit during the process of melting. The computational fluid dynamics (CFD) technique has been utilized for the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Dekhil et al 84 and Rana et al 268 found that the melting time of the shell-andtube LHS system was reduced with the incorporation of fins, and the melting and solidification rate of longitudinal fins were twice of plain tubes and 1.14 times of the radial finned tubes. Amer et al 269 and Abreha et al 270 found that the melting time and solidification of the finned shell-and-tube LHS system were reduced by up to 70.5% by increasing the HTF flow rate and HTF inlet temperature. Shaker et al 271 found that the complete melting and solidification time of cylindrical encapsulated PCM was enhanced by 41% with increasing the fin number from 4 to 12.…”
Section: Thermal Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Dekhil et al 84 and Rana et al 268 found that the melting time of the shell-andtube LHS system was reduced with the incorporation of fins, and the melting and solidification rate of longitudinal fins were twice of plain tubes and 1.14 times of the radial finned tubes. Amer et al 269 and Abreha et al 270 found that the melting time and solidification of the finned shell-and-tube LHS system were reduced by up to 70.5% by increasing the HTF flow rate and HTF inlet temperature. Shaker et al 271 found that the complete melting and solidification time of cylindrical encapsulated PCM was enhanced by 41% with increasing the fin number from 4 to 12.…”
Section: Thermal Enhancementmentioning
confidence: 99%
“…Amagour et al 91 proposed an improved PCM-based coil tube heat exchanger configuration with 13 complete copper fins of 248 mm (long) × 50 mm (high) × 0.9 mm (thick) and 37 copper fins with dimensions of 248 mm × 25 mm × 0.9 mm, which can reduce the melting time by 9% compared with the original configuration. Xu et al 274 and Amer et al 269 concluded that the coupled effects of fin number, location, length, and thickness should be considered comprehensively to obtain an optimal fin structure. The critical value of total fin length was also proved to be increased with the increasing of the Rayleigh number…”
Section: Thermal Enhancementmentioning
confidence: 99%
“…They discovered that the staggered distribution of fins can improve the melting and heat charging rate by 37.2 and 59.1%, respectively. Amer et al [ 13 ] examined the melting process in a PCM-filled shell-and-tube (SAT) unit with a various number of circular fins. They showed that with 36, 30, 18, and 6 fins, 72, 72, 66, and 53% of melting rate enhancement can be obtained compared to the base SAT unit without fins.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has a broad application prospect. However, the low thermal conductivity of phase change materials (PCMs) limits the thermal energy charge/discharge rate of shell‐and‐tube LTESU 4 . For solving this problem, various methods to enhance heat transfer have been proposed by researchers, such as adding nanoparticles, 5,6 metallic foam, 7,8 and fins 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the low thermal conductivity of phase change materials (PCMs) limits the thermal energy charge/discharge rate of shell-and-tube LTESU. 4 For solving this problem, various methods to enhance heat transfer have been proposed by researchers, such as adding nanoparticles, 5,6 metallic foam, 7,8 and fins. 9,10 Compared with other strengthening methods, fins have the advantages of easy manufacture, low cost, and long service life.…”
Section: Introductionmentioning
confidence: 99%